The CLIL (Content Language Integrated Learning) Approach to English Speaking Skill in the industrial Revolution 5.0 era - Susanto, Ferri; Kurniawan, Ildi (Journal of English Education and Teaching, 2025)
This research explored the effectiveness of the Content and Language Integrated Learning (CLIL) approach in improving the speaking skills of Tadris students at State Islamic University Fatmawati Sukarno and State Islamic Institute of Islam Curup Bengkulu. The research specifically focused on integrating CLIL's core aspects: Content, Communication, Cognition, and Culture. A mixed-methods design was used, with qualitative data analyzed via the Huberman and Miles model (data collection, reduction, presentation, and conclusion verification) through observations, interviews, and documentation. Quantitative data was analyzed using a Randomized Solomon Four Group Design and ANOVA. Findings showed that an effective CLIL-based speaking curriculum requires the seamless integration of all four CLIL aspects, grounded in global realities and trending topics. This approach significantly fostered Deep Learning's 6Cs: character, citizenship, collaboration, communication, creativity, and critical thinking, leading to a notable enhancement in students' speaking proficiency. The study also highlighted the crucial role of digital technology collaboration in optimizing this teaching methodology. Quantitative analysis strongly supported these findings, demonstrating a significant positive impact of the CLIL approach on students' English speaking skills, with an F-calculated value (37.276) far exceeding F-table values (2.74 and 4.08).The implications for English language education, particularly within the Tadris programs in Bengkulu, are substantial. The CLIL approach, especially when enhanced by digital support, offers a powerful pedagogical framework for teaching speaking skills. It not only boosts linguistic fluency but also cultivates essential 21st-century competencies crucial for future careers. This research underscores the vital need for developing content-rich, globally relevant curricula that effectively leverage technology to create dynamic and deeply engaging learning experiences.